2016
DOI: 10.1016/j.neuroimage.2015.12.055
|View full text |Cite
|
Sign up to set email alerts
|

The status of the precommissural and postcommissural fornix in normal ageing and mild cognitive impairment: An MRI tractography study

Abstract: The fornix connects the hippocampal formation with structures beyond the temporal lobe. Previous tractography studies have typically reconstructed the fornix as one unified bundle. However, the fornix contains two rostral divisions: the precommissural fornix and the postcommissural fornix. Each division has distinct anatomical connections and, hence, potentially distinct functions. Diffusion weighted MRI and spherical deconvolution based tractography were employed to reconstruct these separate fornix divisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…Metzler-Baddeley and co-workers ( Metzler-Baddeley et al, 2011 ; Metzler-Baddeley et al, 2012b , c ; Christiansen et al, 2016 ) addressed the problem of potential CSF partial volume biases in DTI metrics in MCI patients by applying the bi-tensor Free Water Elimination (FWE) model that fits an isotropic and an anisotropic compartment to the dMRI data and allows for the correction of free water contamination in DTI metrics ( Pasternak et al, 2009 ). The authors compared corrected mean FA, MD, RD and AD metrics for the parahippocampal cingulum, the fornix, and uncinate fasciculus between 25 MCI patients and 20 matched controls ( Metzler-Baddeley et al, 2012b ), with the cortico-spinal tract as a comparison pathway.…”
Section: Diffusion Mri (Dmri) Studies Of the Human Cingulum Bundlementioning
confidence: 99%
“…Metzler-Baddeley and co-workers ( Metzler-Baddeley et al, 2011 ; Metzler-Baddeley et al, 2012b , c ; Christiansen et al, 2016 ) addressed the problem of potential CSF partial volume biases in DTI metrics in MCI patients by applying the bi-tensor Free Water Elimination (FWE) model that fits an isotropic and an anisotropic compartment to the dMRI data and allows for the correction of free water contamination in DTI metrics ( Pasternak et al, 2009 ). The authors compared corrected mean FA, MD, RD and AD metrics for the parahippocampal cingulum, the fornix, and uncinate fasciculus between 25 MCI patients and 20 matched controls ( Metzler-Baddeley et al, 2012b ), with the cortico-spinal tract as a comparison pathway.…”
Section: Diffusion Mri (Dmri) Studies Of the Human Cingulum Bundlementioning
confidence: 99%
“…A previous study employing a similar methodology (Christiansen, Aggleton, et al., 2016) demonstrated that the fornix can also be divided between its precommissural and postcommissural fiber subdivisions (Poletti & Creswell, 1977). The precommissural fornix contains hippocampal connections with the basal forebrain, ventral striatum, and prefrontal cortex, whereas the postcommissural fornix connections reach the medial diencephalon and hypothalamus (Poletti & Creswell, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…The precommissural fornix contains hippocampal connections with the basal forebrain, ventral striatum, and prefrontal cortex, whereas the postcommissural fornix connections reach the medial diencephalon and hypothalamus (Poletti & Creswell, 1977). Using diffusion imaging, the precommissural and postcommissural fibers were found to occupy different locations within the body of the fornix: the postcommissural fornix fibers were located dorsally, whereas the precommissural fibers were located ventrally (Christiansen, Aggleton, et al., 2016). Together with the present results, these findings suggest that there is a topography along the two planes of the fornix, that is, within both the dorsal–ventral and medial–lateral axes of the tract, with both topographies reflecting different sets of hippocampal connections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, diffusion-weighted imaging studies revealed several tracts that connect with the MB, such as the fornix and mammillotegmental tract (Granziera et al, 2011;Kwon et al, 2011;Mori and Aggarwal, 2014;Christiansen et al, 2016;Cacciola et al, 2017;Wei et al, 2017;Kamali et al, 2018;Choi et al, 2019;Maller et al, 2019). Clinical studies also revealed that memory-impaired patients with Korsakoff syndrome exhibit atrophy of the MB (Squire et al, 1990;Harding et al, 2000;Tsivilis et al, 2008;Fama et al, 2012;Kril and Harper, 2012;Aggleton, 2014;Kopelman, 2015;Isenberg-Grzeda et al, 2016;Arts et al, 2017;Johnson and Fox, 2018).…”
Section: Introductionmentioning
confidence: 99%